The Influence of Work Stress and Work Fatigue on Employee Turnover Intentions at PT Pegadaian (Persero) Regional Office VI Makassar - Maharani, Nurfadiza; Adi; Jusri; Nasir, Sri Astuti (Journal of Economics and Management Technologies, 2025)
The aim of this study was to determine the effect of Work Stress and Job Fatigue on the turnover intention of PT Pegadaian (Persero) Regional Office VI Makassar The location of the object of this study was PT Pegadaian (Persero) Regional Office VI Makassar. This researcher used a quantitative approach and data collection by using a questionnaire. In this study, two independent variables were used, namely (X1) Job Stress and (X2) Job Fatigue and one dependent variable, namely (Y) turnover intention. The sample needed in this study was 54 respondents, and the data analysis techniques used were validity test, reliability test, multiple linear regression, t test, f test, and R2 determination coefficient test. This test was carried out using SPSS software version 26. Based on the results of the study, it was found that Based on the results of the t test, it shows that the work stress variable partially has a positive and insignificant effect on turnover intention, the work fatigue variable partially has a positive and significant effect on turnover intention, the work stress and work fatigue variables simultaneously have a positive and significant effect on turnover intention.